Postcolonial theory and false dichotomies - Bobako, Monika (Historein, 2013)
The very conceptual framework that structures Chris Lorenz’s argumentation in his book Bordercrossing is based on the contraposition of the two epistemological perspectives, named as “objectivism” and “relativism”, that are both supposed to be overcome in Lorenz’s own analysis. However, this framework is responsible for a number of interpretative inadequacies in Lorenz’s book – mainly because it is unable to grasp the ways in which power relations influence knowledge production processes and to account for the situatedness of any knowledge, including the one produced in a discipline of history.